Role of field and professional practice in formation competitive professionals with high intellectual potential (Experimental biology, 2015)
Educational, industrial and diploma practices given in fish breeding farms are very important for professional establishment of “6М080400 – Fish industry and commercial industry” specialty students. During the practices students have got methods of fish investigation and obtain necessary knowledge for degree diploma doing.
Keywords: Fish industry and commercial industry” specialty professional practice; ichthyology; Hydrobiology; student; professional technician; manufacturing practices; pre-diploma practice; research and practice; biological analysis; morphological analysis